A Review of the Introduction to Artificial Intelligence for the Analysis of Literary Works and Social Media - Dr. Keikhosrokiani; Dr. AR Costa- Ralha (Al-Qanṭara, 2023)
Artificial intelligence (AI) is the capacity of a digital computer or robot operated by a computer to carry out actions frequently performed by intelligent beings. The phrase is widely used in reference to the effort to create artificial intelligence (AI) systems that possess human-like cognitive abilities like the capacity for reasoning, meaning-finding, generalisation, and experience-based learning. It has been proven that computers can be programmed to perform extremely complicated tasks—like, for example, finding proofs for mathematical theorems or playing chess—with remarkable proficiency ever since the development of the digital computer in the 1940s. Nevertheless, despite ongoing improvements in computer processing speed and memory space, there are currently no programmes that can match human adaptability across a larger range of activities or those needing a substantial amount of background knowledge.